A narrative review of conductive education as professional practice - Annamaria Berger-Jones (Educational Futures)
This narrative review provides an analysis of what is known about conductive education (CE) as professional practice and how that knowledge came to be; it synthesises over one hundred Hungarian and English language publications from 1967 to 2024. The review offers a succinct overview considering political and cultural contexts, clarifying some misconceptions surrounding CE and their impact on the profession. Therefore, it is aiming to open up possibilities to (re)discover CE’s pedagogic value in the present.